In vitro cytotoxicity and druglikeness of pyrazolines and pyridines bearing benzofuran moiety - Asma S. Al Wasidi, Ashraf S. Hassan, Ahmed M. Naglah& (Journal of Applied Pharmaceutical Science, 2020)
A series of pyrazolines and pyridines bearing benzofuran moiety (M1–M10) were synthesized for evaluation of their in vitro cytotoxicity against MCF-7 and HepG2 cell lines. Furthermore, in silico drug-likeness study was carried out. The result of the cytotoxicity of M1–M10 showed that some compounds displayed cytotoxic activity against MCF-7 and HepG2 cells. An assessment of in silico drug-likeness study of M1–M10 illustrates that some compounds showed an agreement to the Lipinski, Ghose, Veber, Egan, and Muegge rules with orally bioavailable.
Keywords: Pyrazoline, pyridine, benzofuran, cytotoxic activity, druglikeness.